Exchange rate behavior with negative interest rates: Some early negative observations - Allaudeen S. Hameed; Andrew Rose (Asian Development Bank Institute (ADBI), 2017)
This paper examines exchange rate behavior during the recent period with negative nominal interest rates. We use a daily panel of data on 61 currencies from January 2010 through May 2016, during which five economies - Denmark, the European Economic and Monetary Union, Japan, Sweden, and Switzerland - experienced negative nominal interest rates. We examine both effective exchange rates and bilateral rates; the latter typically measured against the Swiss franc since Switzerland has had the longest period of negative nominal rates. We examine exchange rate volatility, exchange rate changes, deviations from uncovered interest parity, and profits from the carry trade. We find that negative interest rates seem to have little effect on observable exchange rate behavior.
Keywords: F31; G15; 330; Finance sector development; China; People's Republic of; India; Indonesia; Japan; Korea; Republic of; Pakistan; Taipei; China